Balance of the main cyber crimes that occurred in the municipality of Belém/PA in the period 2018 to 2020 (Research, Society and Development, 2022)
This study aimed to investigate the dynamics of cyber crimes that occurred in the city of Belém/PA in the period 2018 to 2020, making a survey of the most prevalent cyber crimes, classifying them, in addition to identifying the profile of victims of this type of crime. In order to achieve this objective, in this study, procedures derived from bibliographical, documental and field research were used. For the field research, statistical data was collected, referring to cyber crimes, produced by the Secretariat of Public Security of the State of Pará. and analysis of large amounts of data. Therefore, the study focuses on a quantitative approach, statistical analysis and data interpretation. The data made it possible to identify that the most prominent crime was the crime of Estelionato, followed by crimes against honor (slander, libel and defamation) and the crime of invading a computer device. It was noted in the profile of victims that, in terms of gender, the highest prevalence was female; regarding profession, victims were identified in the most varied and independent professional segments; in relation to age group, the highest prevalence is among adults aged 35 to 65 years old; The Belém region with the highest incidence of cybercrime is in the central district of the city, where the upper middle class neighborhoods of the capital of the State of Pará are concentrated.